Odd-even effects in the structure and thermal stability of carboxylic acid anchored monolayers on naturally oxidized aluminum surface - Cegiełka, Daria; Bodek, Łukasz; Zharnikov, Michael; Cyganik, Piotr (The journal of physical chemistry letters, 2025)
Self-assembled monolayers (SAMs) are broadly used for molecular engineering of surfaces and interfaces, which demands control over their structure and properties. An important tool in this context is the so-called odd-even effects exploiting the dependence of the SAM structure on the parity of the number of building blocks forming the backbone of SAM-building molecules. Even though these effects influence parameters crucial for SAM applications, they have been mainly studied on coinage metals (Au and Ag) until now. Here, using the series of biphenyl-substituted carboxylic acids (BPnCOO, n = 0-4), we show that structural odd-even behavior occurs as well on technologically relevant surface of naturally oxidized aluminum (representative of other oxide surfaces), with the even-numbered monolayers exhibiting higher packing density and lower molecular inclination than the odd-numbered analogs. Despite these structural changes, the SAM desorption energy remains nearly constant at a high value (∼1.5 eV) making BPnCOO/AlOx a promising system for organic electronics applications.